LOCAL FEATURES OF THE “KUYOV SINAR” CEREMONY FROM WEDDING CEREMONIES OF THE TASHKENT REGION - Asatillo SUNNATILLAEV (Western European Studies, 2025)
The songs express the great power of the people's spirituality, the creator, and the unwavering will of the working masses. It calls people to spiritual vigor, courage, diligence, humanity, friendship, and loyalty. Songs, regardless of their theme and content, penetrate the human heart with perfect words, melody, and performance. Ceremonial songs are also an ancient treasure of our people, and in all periods, they have contributed to the formation of people as spiritually elevated individuals with their educational influential ideas. The genres of wedding folklore are distinguished by their diversity
Keywords: Ceremony; wedding songs; folklore; poem